Association between tobacco use, depression, and anxiety: A cross-national study among university students from 30 low- and middle-income countries. Issue 6 (11th December 2017) - Peltzer, Karl; Pengpid, Supa
Abstract : This study aimed to investigate the association between tobacco use and depression and anxiety in a cross-national study among university students from 30 predominantly low- and middle-income countries. Self-report survey data were collected from 23 073 university students (58.0% female), with a mean age of 20.8 years (SD = 2.5). Following logistic regression analyses, tobacco using university students were more likely to have depressive symptoms and anxiety (posttraumatic stress symptoms = PTSS) than non-tobacco using students. Gender stratified analysis found associations between tobacco use and depressive symptoms were stronger among women than men. The associations between tobacco use and anxiety (PTSD) symptoms were stronger among men than women. In this large cross-national study, current tobacco use was significantly associated with depression and anxiety (PTSD) symptoms. Tobacco use prevention efforts can help alleviating mental health problems among university students.